2003
DOI: 10.2322/tjsass.46.186
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Transonic Flows around a Thin Wing with an Aileron

Abstract: The experimental airplanes of Supersonic Transportation, SST, are being developed in Japan. The wings are thin to augment cruise aerodynamic performance. If these wings are equipped with ailerons, the shock wave motions on the ailerons might cause aileron buzz not accompanied by heavy separation of the boundary layers. On the other hand, unsteady aerodynamics research regarding thin wings has not been extensive. In order to precisely investigate the shock wave motions on thin wings, two-dimensional CFD simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Tamayama et al [4] used two-dimensional CFD method to investigate the influences of shock wave motion upon aileron hinge moment. The results showed that the imaginary component of the unsteady aileron hinge moment will reach the maximum and positive value when the shock wave oscillates around the midchord on the aileron.…”
Section: Introductionmentioning
confidence: 99%
“…Tamayama et al [4] used two-dimensional CFD method to investigate the influences of shock wave motion upon aileron hinge moment. The results showed that the imaginary component of the unsteady aileron hinge moment will reach the maximum and positive value when the shock wave oscillates around the midchord on the aileron.…”
Section: Introductionmentioning
confidence: 99%